Labor force participation, job search effort and unemployment insurance in the laboratory - Wolfgang Lechthaler; Patrick Ring (Kiel Institute for the World Economy (IfW), 2020)
How the provision of unemployment benefits affects employment and unemployment is a debated issue. In this paper, we aim at complementing theoretical and empirical contributions to this debate with a laboratory experiment: We simulate a job market with search effort and labor force participation decisions while varying the maximum length of unemployment benefit eligibility. Our results reveal two separable, opposing effects: Individuals within the labor force search with lower effort when unemployment benefits are extended. However, individuals are more likely to participate in the labor force and to actively search for a job. Concerning employment, the second effect dominates so that unemployment benefits raise employment.
Keywords: E70; J21; J65; 330; Job Search; Employment; Labor Force Participation; Unemployment Insurance; Economic Recession; Laboratory; Experiment